Protective effects of naringenin and naringin in organ ischemia/reperfusion injuries: a comprehensive narrative review - Hou, Min; Wei, Daiyan; Wang, Yanshun; Zhang, Xiaojian; Yao, Zhiwei (Frontiers in Pharmacology, 2026)
Ischemia/reperfusion injury (IRI) refers to a condition in which ischemia is followed by reperfusion, leading to an exacerbation of the initial tissue damage. Currently, there are no specific therapeutic methods for IRI. Phytochemicals from natural products have the potential to develop noble drugs for IRI. Naringenin (NGE) and naringin (NG) are natural dietary flavonoids derived from ethnobotanical plants in Southeast and South Asia. NGE and NG have a wide range of pharmacological properties, including antioxidant, anti-apoptotic, and anti-inflammatory effects. As research on NGE and NG deepens, it has been found that they protect against IRI. We first summarize plant species containing NGE and NG from Southeast and South Asia in this article. Then, we highlight recent advances in NGE and NG for treating IRI in the myocardium, brain, intestines, kidneys, retinal, liver, spinal cord, skeletal muscles, and testicles. We find that NGE and NG possess antioxidant, anti-inflammatory, anti-apoptotic, anti-endoplasmic reticulum stress, anti-ferroptosis, anti-pyroptosis, and autophagy regulatory properties that protect organs from IRI. In addition, NGE and NG alleviate organ IRI through certain signaling pathways, including nuclear factor-κB, nuclear factor erythroid 2-related factor 2, phosphatidylinositol 3-kinase/AKT, cyclic guanosine monophosphate–adenosine monophosphate synthase–stimulator of interferon genes, sirtuin (SIRT) 1/SIRT 3, and hypoxia-inducible factor-1α. Furthermore, we investigate the interactions between these signaling pathways and inflammation, oxidative stress, and programmed cell death. Nevertheless, NGE and NG still face challenges related to pharmacokinetic interactions, bioavailability, and clinical safety assessments. Further studies will be needed to verify their safety and efficacy in clinical settings.